Law Politics Of Legislative Election - Ika Yuana Darmayanti (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Elections in democracies, including in Indonesia, a process that put people's sovereignty completely hands of the people themselves. Principles of Election in accordance with the constitution, namely the principle of constitutional life of the sovereignty of the people (democracy), it is marked by every citizen has a right to participate actively in the decision-making processes of the state. In Indonesia until today there are several general election, such as the General Election to the The House of Representatives (DPR), Provincial DPRD, Regency / City; Election of the President; and Election Regional level is for election Regent / Mayor. At the village level do Democracy party called Pilkades (Village Head Election).The position of the House of Representatives is strong, the Parliament can not be dissolved by the President, unless the members are all concurrently be members of the People’s Consultative Assembly (MPR). Therefore, Parliament can always keep an eye on the actions of the President, and if it considers the President actually violate the state policy which has been established by the Constitution or the Assembly, the Assembly may be invited to a special court order that could have asked for an answer to the President. Parliament consists of 560 members from 77 constituencies be represented compound (multi-member electoral districts) that have three to ten seats per constituency (depending on population-related region division) selected through open proportional system. The parliamentary threshold of 3.5 per cent applies only to the The House of Representatives (DPR) and does not apply to Provincial DPRD. Keywords: Elections; Democracy; The House of Representatives.